Differences in motoric function of masticatory and facial muscles post segmental mandibulectomy and hemimandibulectomy - Karyono, Ariyanto Suryo; Hardianto, Andri; Riawan, Lucky (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: The highest predilection for jaw tumors is located in the mandible. One of the management of tumors in the mandible is resection. The resection will result in a discontinuity in the jaw and disruption of the stomatognathic system, one of which is a decrease in the motoric function of the masticatory muscles. Electroneuromyography (ENMG) is a type of examination that includes an electroneurography (ENG) examination, which includes a Neural Conduction Study (NCS) based on stimulation value (STIM) and velocity (VEL), and electromyography (EMG) which can be used to assess motoric function impairment of masticatory and facial muscles in patients undergoing mandibular resection. This study analyzed the differences in the motoric function of masticatory and facial muscles post-segmental mandibulectomy and hemimandibulectomy. Methods: This preliminary analytical cross-sectional study compares ten post-segmental mandibulectomy or hemimandibulectomy patients who had undergone mandibular reconstruction in the Oral Surgery Department of Hasan Sadikin Hospital Bandung. Assessment was performed using an AO plate (Arbeitsgemeinschaft für Osteosynthesisfragen) towards the patients. The results were compared using Chi-Square and Mann-Whitney statistical analysis. Results: A decrease in masticatory muscle function was detected using ENMG. NCS and EMG assessments were obtained. There was no significant difference in NCS values (p>0.05) in patients with segmental mandibulectomy (mean STIM 4.2 ± 1.7, VEL 13.23 ± 5.38) and hemimandibulectomy (mean STIM 4.3 ± 1.35, VEL 12.56 ± 4.83), however, a significant difference was found in the EMG values (p=0.025; p<0.05) of the patients with segmental mandibulectomy (mean 70% of patients were normal) and hemimandibulectomy (mean 20% of patients were normal). Conclusion: There are differences in the decreased motoric function of masticatory and facial muscles post-segmental mandibulectomy and hemimandibulectomy.Keywords: motoric function; masticatory muscles; facial muscles; mandibular resection